PENGARUH EDUKASI TERHADAP PENGETAHUAN DAN SIKAP IBU TENTANG PEMBERIAN ASI EKSKLUSIF DI RSIA MURNI TEGUH ROSIVA MEDAN - Ginting, Monika; Simanullang, Rostime Hermayerni (Indonesian Trust Nursing Journal, 2025)
Infants aged 0-6 months require exclusive breastfeeding as their primary source of nutrition. However, some mothers opt not to breastfeed and instead provide formula milk, possibly due to a lack of education. The objective of this study is to determine the effect of education on mothers' knowledge and attitudes regarding exclusive breastfeeding. This study method is pre-experimental research using a one-group pre-test and post-test design. The research was conducted at Murni Teguh Rosiva Hospital. The population consisted of 51 individuals, with a sample size of 45 participants selected through purposive sampling. Analysis was performed univariately using frequency distribution tables and bivariately using the Paired Sample T-Test, as the data were normally distributed. The study showed that before education, the majority of mothers had moderate knowledge (93.3%), which improved to good knowledge (80.0%) after education, with an average pre-test score of 9.22±1.580 and a post-test score of 12.82±1.585. Before education, 60.0% of mothers had a positive attitude, which increased to 100.0% after education, with an average pre-test score of 34.42±5.450 and a post-test score of 46.33±3.045. The provision of education significantly influenced mothers' knowledge and attitudes regarding exclusive breastfeeding at Murni Teguh Rosiva Hospital, with a p-value of 0.000 < 0.05. It is concluded that there is a significant difference in mothers' knowledge and attitudes before and after education. It is recommended for future researchers are encouraged to conduct further studies on mothers' knowledge and attitudes regarding exclusive breastfeeding.